Rapp-Hodgkin ectodermal dysplasia syndrome - Stasiowska, B (1981)
We report a mother and daughter with Rapp-Hodgkin ectodermal dysplasia syndrome. Features of the previously described cases were confirmed, although no growth deficiencies were observed. Autosomal dominant inheritance was probable although X-linked transmission could not be excluded.